Modeling and simulation of the elastic properties of natural fiber-reinforced thermosets - Alhijazi, Mohamad; Safaei, Babak; Zeeshan, Qasim; Asmael, Mohammed (Wiley, 2021)
This paper presents an analysis on the elastic characteristics of luffa and palm natural fiber composites (NFC) with epoxy and ecopoxy matrixes, taking into account the impact of fiber volume fractions. Furthermore, longitudinal modulus, transverse modulus, shear modulus, and Poisson's ratio were predicted using representative volume elements (RVEs) with chopped random and unidirectional fiber arrangements. However, analytical approaches such as rule of mixture, Chamis, Halpin-Tsai, and Nielsen were considered for validating and comparing the findings of finite element analyses. Hence, it was found that increasing fiber volume fraction increased the elastic properties of palm/epoxy, palm/ecopoxy, and luffa/epoxy NFCs, but decreased that of luffa/ecopoxy NFC. Addition of palm fibers in ecopoxy and epoxy had stronger effect than luffa on enhancing the elastic properties of the final structure. However, greatest elastic characteristics observed through analytical and numerical models were obtained for ecopoxy matrix with 0.5 palm fibers. A strong agreement was observed between the results obtained from analytical approaches and RVE unidirectional model. Chamis model exhibited higher outcomes compared to the considered analytical techniques, while Halpin-Tsai model showed the least values.
Keywords: finite element analysis; Luffa fibers; natural fibers composites; palm fibers; representative volume element